The indigenous cattle of Ethiopia. Part I - Alberro, M.; Haile-Mariam, S. (1982)
The recent FAO/UNEP consultation on Animal genetic resources conservation and management stressed the importance of indigenous, adapted breeds of cattle. Relatively little is known of the indigenous cattle breeds of Ethiopia. This article, in describing the breeds and their environmental background, shows the considerable potentialities of many of them. The article is in two parts: Part I, in this issue of world Animal review, deals with the origin and classification of the breeds and includes descriptions of a number of the breeds; Part II will be in the issue no. 42 and will contain descriptions of the remaining breeds.